Lifelong Islamic Education in Early Islamic Tradition: A Hadith Study on the Scholarly Mobility of the Prophet’s Companions - Zuhrah, Ni'matuz; Azwar, Muhammad (Dirasah: Jurnal Pendidikan Islam, 2026)
Education is the defining factor of a civilisation; it has evolved over time through a variety of concepts. In the early days of Islam, the concept of lifelong learning was already being practised. This concept was embedded in the intellectual life of the Muslim community, as evidenced by the learning activities undertaken by the Prophet and his companions. In the modern world, this concept has been widely introduced and promoted by national and international organisations, yet its implementation remains limited to conceptual frameworks and the preparation of supporting facilities. This study aims to examine in greater depth the application of the concept of lifelong learning within the tradition of Islamic education. This study examines the practice of knowledge transmission during the time of the Prophet. The research was conducted by examining hadiths that describe the learning processes taking place amongst the Companions from various backgrounds. The results of this study indicate that the practice of lifelong learning was already in place during the time of the Prophet; this was manifested through education that transcended age, social status, geography, and gender, as well as through lifelong learning. This research demonstrates that the practice of lifelong learning was already being practised by the Companions; it is not a new concept of the modern era, but has been part of the Islamic intellectual tradition for centuries